Unlocking Consumer Satisfaction: How Product Quality, Service Quality, and Preferences Drive Hydroponic Lettuce Purchases - Rizki Ramadhan, Mohammad Akbar; Sastrya Wanto, Hary; Wisnujati, Nugrahini Susantinah (PT. Sangadji Media Publishing, 2024)
This study aims to analyze the model of purchasing decisions and their impact on consumer satisfaction when buying hydroponic lettuce. It specifically investigates how product quality, service quality, consumer preferences, and purchasing decisions directly affect consumer satisfaction. Additionally, it examines the indirect influence of product and service quality on consumer satisfaction through purchasing decisions. Utilizing a quantitative research methodology, data was collected via a structured questionnaire employing a Likert scale to measure respondents' attitudes. The sample consisted of 75 consumers of hydroponic lettuce from Level One MSMEs. The analysis involved various statistical tests, including outer model testing for validity and reliability, goodness-of-fit assessments, and hypothesis testing to explore the relationships among five key variables: purchasing decisions, consumer satisfaction, consumer preferences, service quality, and product quality. Findings indicate that while product quality does not significantly influence purchasing decisions, both service quality and consumer preferences have substantial effects on these decisions, ultimately impacting consumer satisfaction. Moreover, the study highlights the importance of understanding the multifaceted factors influencing consumer decision-making, suggesting that future research should explore a broader range of products and additional variables, such as brand loyalty, to gain deeper insights into consumer behavior.